A Magnetically and Thermally Controlled Liquid Metal Variable Stiffness Material. Issue 6 (17th November 2022) - Zhang, Mingkui; Chen, Xuanhan; Sun, Yongwei; Gan, Minfeng; Liu, Maze; Tang, Shi-Yang; Zhang, Shiwu; Li, Xiangpeng; Li, Weihua; Sun, Lining
Abstract : Smart materials that can actively tune their stiffness are of great interest to many fields, including the construction industry, medical devices, industrial machines, and soft robotics. However, developing a material that can offer a large range of stiffness change and rapid tuning remains a challenge. Herein, a liquid metal variable stiffness material (LMVSM) that can actively and rapidly tune its stiffness by applying an external magnetic field or by changing the temperature is developed. The LMVSM is composed of three layers: a gallium–iron magnetorheological fluid (Ga–Fe MRF) layer for providing variable stiffness, a nickel–chromium wire layer for Joule heating, and a soft heat dissipation layer for accelerating heating and rapid cooling. The stiffness can be rapidly increased by 4 times upon the application of a magnetic field or 10 times by solidifying the Ga–Fe MRF. Finally, the LMVSM is attached to a pneumatically controlled soft robotic gripper to actively tune its load capacity, demonstrating its potential to be further developed into smart components that can be widely adopted by smart devices. Abstract : A liquid metal variable stiffness material (LMVSM) that can actively and rapidly tune its stiffness by applying an external magnetic field or by changing the temperature is developed. The LMVSM can be attached to a pneumatically controlled soft robotic gripper to actively tune its load capacity, demonstrating its potential to be adapted by various smart devices.